FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENGGUNAKAN TEKNOLOGI PADA BUDIDAYA MANGGIS DI JAWA BARAT - Dini Rochdiani; Sulistyodewi Nur Wiyono; Kuswarini Kusno; Lies Sulistyowati; Yosini Deliana; Sri Fatimah; Gema Wibawa Mukti (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
Mangosteen (Queen of Tropical Fruit) is one of the excellent commodities of Indonesia's flagship fruit export which contributes  to the country's foreign exchange and farmer's income, with the aim of exporting Hong Kong, Taiwan, China. The biggest centers of mangosteen production in Indonesia are West Java, including Tasikmalaya and Purwakarta. Because mangosteen has health benefits, the demand for mangosteen fruit is increasing (50%/year) and this makes it an opportunity to develop mangosteen agribusiness for Indonesian farmers. Many factors influence farmer decisions, especially in the application of cultivation technology, causing national mangosteen production to be unstable and of low quality. This condition causes Indonesian mangosteen to be unable to compete with other countries such as Malaysia, Thailand and Latin America. The amount of mangosteen produced by farmers for export purposes is still low. Useful cultivation techniques and technology applications are not yet fully compliant with the Standard Operating Procedures (SOP) and Good Agricultural Practices (GAP), such as the use of superior seeds, dosage methods and times of fertilization, observation and control of pests, and harvest and post-harvest treatment. this is identifying the factors that influence farmers' decision to use technology in mangosteen cultivation. The research method used was a survey of 69 mangosteen farmers selected by simple random sampling and location selected by multistage random sampling. The factor analysis was used Regression  with System Equations Model. The results of the study show that the factors that influence farmers' decision to use mangosteen cultivation technology to increase production and quality of crops are farmers' assets, namely physical assets, non-physical assets and access to farmers' access. Physical assets, namely the number of ownership of trees, rice fields, vehicles, and income outside of farming; Non-physical assets, namely the number of productive age family members, farmers' access assets, namely the length of travel time from the garden to the provincial road.